Impact of root rot on the yield of winter wheat varieties under steppe conditions - Matiukha, V.; Tsyliuryk, O.; Pedash, T.; Semenov, S. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2025)
Goal. To determine the level of development and spread of root rot in winter wheat varieties and the formation of yield depending on predecessors and sowing dates.Methods. The research was conducted in 2021—2023 at the experimental field of the Institute of Grain Crops of the NAAS of Ukraine, located at the Dnipro Experimental Farm (Dnipro, Ukraine). Agrotechnical measures for winter wheat cultivation followed generally accepted recommendations. The predecessors of winter wheat were black fallow, pea, and sunflower. The experiment used Ukrainian-bred winter wheat varieties, namely Blahodatna, Liha Odeska, Podolianka, and Bohdana.Results. Root rot infestation of winter wheat depended on the variety, predecessor, and sowing date. The least susceptible was Blahodatna, where disease spread was 8—12% lower and development 4—6% lower compared to the most vulnerable varieties, while Liha Odeska and Bohdana showed the highest infestation (84—96% spread and over 40% development after pea and late sowing). Optimal sowing dates ensured minimal infestation — only 43—52% after black fallow with 2.5—6% development, whereas late sowing increased the disease to 70—96 % with up to 45% development. Yield largely depended on the combination of sowing date and predecessor: the optimal date provided 4.83—5.94 t/ha, which was 0.4—0.7 t/ha (7—12%) higher compared to early and late sowings. Black fallow contributed to a yield increase of 0.6—0.8 t/ ha (12—15%) compared to sunflower and 0.3—0.5 t/ha (6—9%) compared to pea. Among the varieties, Liha Odeska showed stable productivity, Blahodatna provided a uniform yield level, while Podolianka and Bohdana were more variable.Conclusions. The Blahodatna variety was the least affected by root rot, while the highest yields (4.83—5.94 t/ha) under the Northern Steppe conditions were ensured by the Liha Odeska variety when sown at the optimal time after black fallow.